PENGARUH KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN DAN PENDAPATAN RUMAH TANGGA TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (STUDI KASUS DI KECAMATAN PACE, KABUPATEN NGANJUK) - Ahmad Anas Murtado (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Land and Building Tax is an important income for each region, therefore each local government has its own way of optimizing the amount of local revenue (PAD), especially the Land and Building Tax sector. This study aims to determine the effect of taxpayer awareness, tax sanctions, and household income on taxpayer compliance in paying PBB in Pace District, Nganjuk Regency, either partially or simultaneously. The approach in this study is a quantitative approach using multiple linear regression tests and the SPSS software tool for Windows version 23. The research was conducted in Pace District, Nganjuk Regency with a population of all land and building tax payers in Pace District, Nganjuk Regency and the number of samples obtained by 100 respondents. The conclusions of the results of this study are (1) taxpayer awareness partially has a significant effect on taxpayer compliance in paying PBB. (2) Tax sanctions partially have a significant effect on taxpayer compliance in paying PBB. (3) Household income partially has a significant effect on taxpayer compliance in paying PBB. (4) Taxpayer awareness, tax sanctions, and household income simultaneously have a significant effect on taxpayer compliance in paying PBB.